Inhibition and dissolution of wax deposition for phet crude in a semi-pilot scale using poly(ethylene-co-vinyl acetate) - Perapon Sirijitt (Chulalongkorn University, 2014)
Thesis (M.S.) -- Chulalongkorn University, 2007